Fintech Adoption and its Impact on Sustainability: Risk Benefit Analysis of an Emerging Economy - Sadiq, Naila; Baneen, Ummul; Abbas, Syeda Fizza (Audit and Accounting Review, 2023)
This study aims to analyze how the six variables, such as perceived legal risk, perceived performance risk, perceived cyber risk, perceived financial risk, perceived economic benefit, ease of use, and monetary benefit affects the adoption of financial technology, with the moderating effect of gender and education. Additionally, it explores the impact of Fintech adoption on economic, environmental, and social sustainability of Pakistan. For this purpose, a quantitative research approach has been employed by using a well-designed questionnaire. Moreover, the sample size of 312 was considered and the responses were collected through Google forms. The data collected was then analyzed using SPSS. The study’s findings revealed that the perception of the advantages of using fintech has a positive impact on its adoption. The perception of risk has a negative impact, however, this impact is much lesser than the benefits. Risk perception negatively impacts sustainability while benefits perception impacts sustainability positively. Thus, this study can provide policymakers in emerging economies with valuable insights into the perceived risks and benefits of Fintech adoption for sustainable development. This study gives insight to the practitioners and researchers on how perceived risk and benefit can impact Fintech adoption and how its adoption, in turn, impacts sustainability. The research can contribute to informed policy decisions, support the development of robust regulatory frameworks, advance knowledge, and promote inclusive growth in emerging economies.